Comparison of country risk, sustainability and economic safety indices - Stankevičienė, Jelena; Sviderskė, Tatjana; Miečinskienė, Algita (Business: Theory and Practice, 2014)
Country risk, sustainability an economic safety are becoming more important in the contemporary economic world. The aim of this paper is to present the importance of comparison formalisation of country risk, sustainability, and economic safety indices for strategic alignment. The work provides an analysis on the relationship between country risk, sustainability an economic safety in EU countries, based on statistical data. Investigations and calculations of rankings provided by Euromoney Country Risk Index, European Economic Sustainability Index as well as for Economic Security Index were made and the results of EU country ranking based on three criteria were provided. Furthermore, the data for the Baltic States was summarised and the corresponding index of consistency for random judgments was evaluated.